Experimental study on the influence of sample preparation and testing methods on the shear mechanical properties of silt - Shige Wang; Yanlong Li; Sen Li; Jintao Liu; Zongling Zhang; Tianyou Lu (Scientific Reports)
Abstract To investigate the influence of sample preparation conditions and testing methods on the shear properties of compacted silt, samples with different moisture contents were prepared by saturation and drying methods. The shear mechanical properties of the samples were tested by direct shear and triaxial compression tests. When the designed moisture content w d of the sample is lower than the optimal moisture content w op, the structural strength of the drying sample is higher than that of the water-added sample, and the brittle failure is more obvious in the drying method, and the shear strength and parameters are larger. This is due to the influence of the gradation properties of the silt and the stress history in the process of sample preparation. When the intended water content of the sample is higher than the optimal water content, the mud particles are easily adjusted, and the deformation and stability process before shearing makes the two sample structures tend to be the same. So that the failure trend and shear strength properties are close to each other. Under the influence of the stress state of the sample in the direct shear and triaxial test and the uniformity of the distribution of clay particles in the water addition method, the change rule of the aggregate strength of silt particles on the shear surface is different with the thickness of the water film. The change rule of shear strength and water addition method parameters differs with the change of w d, while the shear strength and drying method parameters decrease with increasing w d.